KAJIAN SEMIOTIKA PADA PUISI EMBRIO, LELAKIKU, DAN SPORA KARYA OKA RUSMINI - Lulu Lutfianingrum; Iqbal Sidik; Dian Hartati (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2022)
Poetry is a depiction of meaning through a process of contemplation and imaginative experience then arranged in the form of words so that the reader can feel the meaning conveyed by the poet through writing. The study of poetry through the realm of semiotics is more interesting because this study discusses how to study a poem by enjoying the markers that are built into a work with the beauty of language. This study was also structured with the aim of enriching the reader's knowledge by dissecting the semiotics contained in the poems